Model for implementing lean manufacturing in small and medium-sized engineering organisations. (30th July 2019) - Shah, Sandip M.; Murugesh, R.; Devadasan, S.R.
In this paper, the theory of a model for implementing lean manufacturing (LM) in small and medium engineering organisations (SMEOs) has been presented. This model was given the name 'LEMSEO' (stands for lean manufacturing in small-sized engineering organisations). LEMSEO has been designed to successfully implement LM in SMEOs in three phases. In the first phase, the awareness about implementing LM in the SMEO is created. In the second phase, the confidence over successfully implementing LM in the SMEO is developed. In the third phase, full fledged LM projects in a sustained manner are implemented. These three phases of LEMSEO model have to be implemented by following 20 steps. After describing the conceptual features of LEMSEO model, the activities to be carried out for implementing these 20 steps are narrated. While concluding this paper, it has been suggested to conduct case studies for examining the practical validity of LEMSEO model.